Changes in antimicrobial resistance patterns and dominance of extended spectrum β-lactamase genes among faecal Escherichia coli isolates from broilers and workers during two rearing periods. Issue 3 (3rd July 2018) - Doregiraee, Fatemeh; Alebouyeh, Masoud; Nayeri Fasaei, Bahar; Charkhkar, Saeed; Tajeddin, Elahe; Zali, Mohammad Reza
Abstract: The emergence of antibiotic-resistant Escherichia coli, especially extended–spectrum β-lactamase (ESBL)–producing strains, in the intestinal tract of broilers could be a threat to poultry and human. We investigated changes of antimicrobial resistance patterns and frequency of ESBL genes among faecal E. coli isolates of broilers and workers in five different farms during two rearing periods in Iran. In this regard, E. coli was isolated from rectal swabs of the workers and cloacal swabs of the broilers. After detection of antibiotic resistance patterns, phenotypic and genotypic characterisation of ESBL phenotype in these strains, carriage of the resistance genes on their crude plasmid extracts and diversity of plasmid profiles were analysed. Accordingly, multidrug-resistant (MDR) patterns were detected in a high percentage of E. coli strains from the workers (72.7%) and poultry (92.3%). ESBL-producing E. coli strains were identified in these farms throughout the two periods of rearing (6.3%). bla CTX-M-1, bla CTX-M-61, bla TEM-116 and bla TEM-1 were characterised in 6 (Period I/II: 4/2), 1 (Period I), 2 (Period II) and 9 (Period I/II: 5/4) strains, respectively. The first isolation of E. coli strains harbouring the bla TEM116 gene in chicken is reported in this study. In conclusion, results of this study showed that chickens could serve as a reservoir for ESBL-producing E. coli strains. These strains could carry clinically important ESBL or new emerging β-lactamases genes. Early colonisation and selection of the resistant strains during rearing periods proposed illegal use of antimicrobials as the cause of change in resistance patterns in the studied farms.